Strategy for Implementing the Bureaucratic Reform of The Regional Government of Bengkulu City - Yohanes Susanto; Shinta Wiji Rahayu (Ilomata International Journal of Management, 2021)
This research will discuss how the Bengkulu City Government's efforts in implementing the bureaucratic reform strategy as a form of realization of Presidential Instruction No.1 of 1995 concerning Improvement and Improvement of Service Quality of Government Apparatus to the Community which refers to the 2014-2025 National RUPM Vision and the RPJPD Vision. Bengkulu Province 2005-2025 and Regional Head Vision 2016-2021. This study uses descriptive qualitative methods with data collection techniques through in-depth interviews and documents. The main focus of this research is the extent to which the Bengkulu City Government bureaucratic reform process is being carried out at BPPT Bengkulu City, and what are the strategies used in implementing the bureaucratic reform. Based on this research, the results obtained show that the bureaucratic reform efforts that are running in the Bengkulu City Integrated Licensing Service Agency still have several obstacles. The strategy used by BPPT Bengkulu City is Incremental Strategy, which is a strategy that is implemented in stages which can be seen from the Vision and Mission, Objectives and Objectives of the DPMPTS Policy Strategy. In its implementation, there are still various obstacles. The bureaucratic reform process is certainly still far from what is expected by the community. BPPT Bengkulu City is expected to be able to solve the problems that have caused the creation of an effective and efficient government.